On the theory of radiation at large effective coupling constant - Fomin, S.P.; Shul’ga, N.F. (Вопросы атомной науки и техники, 2013)
A brief historical overview of one of the direction of investigations of high-energy particle interaction with matter at large values of the effective coupling constant is presented. The treatment is based on an example of ultra relativistic electron bremsstrahlung in an amorphous target and in a crystal when the coherence length is much greater than the particle free path in matter and when the multiple scattering can have a significant impact on the bremsstrahlung process. The comparison of the results of theoretical calculations with the data of recent experiments carried out in SLAC and CERN is given.